Challenges of Offering a MOOC from an LMIC - Pasha, Aamna; Abidi, Syed; Ali, Syed (International Review of Research in Open and Distributed Learning, 2016)
Massive open online courses (MOOCs) were initiated in the early 2000s by certain leading American and European universities. An integral part of the MOOC philosophy has been to provide open access to online learning. Despite their potential advantages to local audiences, faculty and institutions, the number of MOOCs offered from low and middle income countries (LMICs) remains low. The intent of this paper is to provide a reflective perspective on a MOOC recently offered from an LMIC, namely, Pakistan. According to our analysis, the main concern for the organizers of this MOOC was to maintain a high standard of quality, and to offer a course topic that responded to the academic needs of this region. The pedagogical strategy also emphasized on allowing the participants flexibility of time, enabling them to access the course content despite limitations with power shortages, internet speeds, and computer literacy. Despite the lack of resources and expertise, there is significant enthusiasm to introduce this form of teaching and learning to LMIC audiences.